Amanda Pig and Her Best Friend Lollipop - Leeuwen, Jean Van (Penguin Group, 1998)
Amanda loves playing at Lollipop's. But when she finally gets to sleep over at her best friend's house, Amanda realizes that she might like home the best.
Keywords: Animal Stories